CORRELATION BETWEEN SELF-EFFICACY AND PHYSICAL ACTIVITY OF ELDERLY PEOPLE WITH HYPERTENSION - Puspita Hanggit Lestari; Mia Fatma Ekasari; Raden Siti Maryam; Siti Badriah; Verra Widhi Astuti (Jurnal Keperawatan, 2026)
Lack of physical activity in the elderly affects the incidence of hypertension in the elderly. High self-efficacy can help people maintain energy during physical activity. This study aims to determine the relationship between self-efficacy and physical activity in the elderly with hypertension. The research design used is descriptive analytic with a cross-sectional approach involving 106 elderly people. The questionnaires General Self-Efficacy Scale (GSES) and Global Physical Activity Questionnaire (GPAQ). The data analysis in this study used the Chi-Square test. The results of the study found that the self-efficacy of the majority of the elderly was in the high category (52.8%), and physical activity in the majority of elderly with hypertension was in the low category (51.9%). The results of the Chi-Square test showed a relationship between self-efficacy and physical activity in the elderly with hypertension. a p-value of 0.030 (<0.05). Elderly people who have high self-efficacy engage in physical activity in the high category. Self-efficacy plays a role in maintaining motivation to do physical activity. Health workers need to include self-efficacy-boosting and activity interventions to improve the effectiveness of hypertension management programs.